Thermo-economic optimization of CHP systems : from large to small scale applications - Ferreira, Ana C. M. (2011)
There is a growing potential for the use of small-scale cogeneration systems in the building sector, because this systems are able to produce both useful thermal energy and electricity from a single source. This fact represents a significant increase in the efficiency of energy conversion, when compared with the conventional electricity generation. The aim of this paper is the development of a thermo-economic model to optimize a small-scale cogeneration system able to deliver 125kW of thermal power to fulfil the base-heating load of a medium-size building. The objective function was defined as the maximization of the annual worth and six decision variables were also defined. The mathematical model was implemented using the Box method in MatLab® environment. The results show that the small CHP system discloses a positive annual worth for the simulated conditions. The fuel is the most predominant cost, which is significantly greater than the capital investment cost. The positive profits are due mainly to the great income from selling the total electricity that is produced to the grid. The study shows that the most relevant variables in micro-gas turbine system are the compressor pressure ratio, the turbine inlet temperature and the internal pre-heater effectiveness. The optimal solution results are strongly correlated with the electricity and fuel prices and with the components performance/cost assumptions considered in the model.